Effectiveness of Istanbul Protocol Training: A Survey Study for the Students of Criminal Execution and Security Services Program - Akın, Ufuk; Aydın, Faruk (The Bulletin of Legal Medicine, 2024)
Objective: Torture is a violation of human rights which still preserves its importance in today’s world. Istanbul Protocol (IP), is a formative document prepared by many experts working in related fields on the medical reporting of torture and is accepted by United Nations. Our objective in this study was to evaluate the effectiveness of the provision of IP training to students who will probably work as the wardens of the future. Methods: A survey covering twelve statements structured according to IP was administered to 29 volunteers (17 males, 12 females) who second year students of Criminal Execution and Security Services Program. Students were asked to respond to the statements in the survey as agree, disagree, or have no idea. The changes in the answers given before and after the training were examined. Results: A higher rate of correct answers in all statements of the survey was observed after the training and the change acquired in all statements except one was detected to be statistically significant. For instance the rate of those who thought that it would be appropriate for security forces to accompany the examination was 68.9%, and the rate of those who thought that a biological sample could be taken by force was 65.5%. After training, these rates decreased dramatically. Conclusion: In the struggle against human rights violations and torture, the acquisition of information and sensitivity on these subjects by all addressees of the subject is very important and IP training would constitute good means for this aim.